2006
DOI: 10.1098/rspb.2006.3751
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in animal personality traits: does prior experience alter the degree of boldness?

Abstract: Theoreticians predict that animal 'personality' traits may be maladaptive if fixed throughout different contexts, so the present study aimed to test whether these traits are fixed or plastic. Rainbow trout (Onchorhyncus mykiss) were given emboldening or negative experiences in the forms of watching bold or shy individuals responding to novelty or winning or losing fights to examine whether prior experience affected boldness. Bold individuals that lost fights or watched shy demonstrators became more shy by incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
217
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(231 citation statements)
references
References 54 publications
12
217
2
Order By: Relevance
“…an individual  age interaction [31]). Prior experience could increase boldness [39], leading to higher risk-taking behaviour in older males. Variation in individual male plasticity with age was high in all age classes, however, suggesting a cautious interpretation of the individual  age interaction.…”
Section: Results (A) Open-field Testmentioning
confidence: 99%
“…an individual  age interaction [31]). Prior experience could increase boldness [39], leading to higher risk-taking behaviour in older males. Variation in individual male plasticity with age was high in all age classes, however, suggesting a cautious interpretation of the individual  age interaction.…”
Section: Results (A) Open-field Testmentioning
confidence: 99%
“…It should be noted, however, that this plasticity seems to be context dependent. Frost et al (2007) for instance, showed that bold fish appear to be more flexible in changing their behaviour when observing other individuals with opposing personality traits, as compared to shy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al, 2010). In either case, the results suggest that active copers, as opposed to passive copers can be behaviourally characterised by (1) actively trying to escape from a stressor (Silva et al, 2010), (2) showing higher feed motivation after transfer to a new environment (Øverli et al, 2007), (3) being more risk taking and exploratory when exposed to novelty (Øverli et al, 2006;Frost et al, 2007;MacKenzie et al, 2009) and (4) being more aggressive (dominant) during aggressive encounters (Øverli et al, 2004). In addition, active copers exhibit typical neuroendocrine responses such as (1) lower hypothalamus-pituitary-interrenal (HPI) activity (Silva et al, 2010), (2) lower HPI reactivity (Øverli et al, 2005), (3) higher sympathethic reactivity and lower parasympathetic reactivity (measured as opercular beat rate, e.g.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In birds, fish, and rodents, for example, some individuals are consistently more aggressive than others, and aggressive individuals differ from nonaggressive individuals in many other respects like foraging behavior or the exploration of novel environments (5). From an adaptive point of view, both the coexistence of behavioral types and the consistency of individuals are poorly understood (10, 11).Many researchers believe that a fundamental factor structuring personality differences is the degree to which individual behavior is guided by environmental stimuli (6)(7)(8)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Whereas some individuals pay attention to environmental stimuli and quickly adapt their behavior to the prevailing conditions, others show more rigid, routine-like behavior.…”
mentioning
confidence: 99%